The Urgency of a Supervisory Institution for the Regional Government-Owned Enterprises (BUMD) of Banten Province, Indonesia - Ferza, Ray; Hamudy, Moh Ilham A.; Rifki, M. Saidi (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
Based on data from 2016 Indonesia’s Central Bureau of Statistics (BPS), Regional Government Owned Enterprises (BUMD) failed to perform optimally. The condition of BUMDs varies greatly across Indonesia, but most of them lack of clear direction or guidance from a supervising institution. This paper seesk to highlight the urgency of establishing supervisory institution to guide BUMD in Banten Province by examining efforts on behalf of Province Government of Banten in institutionalizing BUMD supervision in three capacities the supervision of BUMD as limited liability companies, regulatory efforts for BUMD supervision, and the establishment of a supervising institution to guide the BUMD. The study employs a descriptive analysis and utilizes a qualitative approch. Data was retrieved through in-depth interviews and focus group discussions. The study found that regulative efforts by Province Government of Banten for the supervision of its BUMD were still at minimum in terms of quantity, and the issued regulations have only concerned on financial performance aspect. The Mid-term Development Plan (Rencana Pembangunan Jangka Menengah Daerah, RPJMD) of Banten province has not included BUMD as one of the determinants of its success. The study has further revealed budget constraints for BUMD supervision, legal ambiguities in the supervision of a Limited Liability Company (PT) BUMD, limited human resources, and a complex legal construction in need of adjustment. Establishing clear and focused institution for the supervision of BUMD is an urgent matter for Banten Province. With one in place, the Province could clearly supervise its BUMDs and government guidance thereof would be more comprehensive, not limited to financial performance control.